Critical Discourse Analysis on the Samsung Mobile Phones Advertisements: Applying Fairclough's 3D Model and Social Semiotic Theory - I Putu Yoga LAKSANA; Luh Gede Eka WAHYUNI; I Nyoman Adi Jaya PUTRA; VIRGINIYA, Putu Tika (Politeknik Negeri Ujung Pandang, 2025)
This study employs critical discourse analysis to examine recent advertising campaigns for mobile phones, focusing on a leading global brand. Conducted purely for academic purposes and not reflecting any official brand positions, our research uses a qualitative approach combining Fairclough’s 3D model and Kress and Van Leeuwen’s social semiotics theory. We analyze both textual and visual aspects of 2023 mobile phone advertisements to decode underlying ideologies. Our multimodal critical analysis reveals how linguistic and visual techniques construct aspirational yet constricting identities and lifestyles revolving around constant consumption of mobile technology. Findings demonstrate that these ads exert rhetorical power by addressing perceived shortcomings in target audiences’ lives and positioning new products as indispensable solutions. Imperatives compel viewers to envision improved lifestyles necessitating regular upgrades, while vibrant images of confident models reinforce ideological influence. This study showcases how critical discourse analysis can uncover subtle sociocultural assumptions and mechanisms of rhetorical influence in mobile technology promotions. It exposes how ads promise meaningful change but ultimately deliver superficial upgrades that sustain corporate interests. The key insight is that while ads link consumption to aspirational identities, a critical examination reveals this diversionary focus hinders pursuit of genuine social change. Our analysis contributes to the broader understanding of advertising discourse and its societal implications.